Effect of Scanning Strategies on the Microstructure and Mechanical Properties of Inconel 718 Alloy Fabricated by Laser Powder Bed Fusion. Issue 5 (9th June 2022) - Liu, Linqing; Wang, Di; Yang, Yongqiang; Wang, Zhi; Qian, Zeyu; Wu, Shibiao; Tang, Jinrong; Han, Changjun; Tan, Chaolin
Abstract : The scanning strategy is an essential factor that determines the thermal history and combination of melt tracks within parts in the laser powder bed fusion (LPBF) process, which can significantly influence the microstructure evolution, defect formation, and mechanical properties of parts. Herein, the effect of scanning strategies (i.e., Y‐scan, XY‐scan, Rot‐scan, and Island‐scan) on the microstructure and mechanical properties of Inconel 718 (IN718) parts manufactured by LPBF is investigated. The results show that different scanning strategies can lead to different morphologies of melt tracks, and the Rot‐scan is the most beneficial strategy for improving density of parts. Different scanning strategies change the direction of the temperature gradient within parts, resulting in different morphologies of grain growth. The tensile properties of samples built with four types of scanning strategies show superior mechanical properties compared with the cast. The ultimate tensile strength of samples manufactured by Y‐scan, XY‐scan, and Rot‐scan is equivalent to that of the wrought, while the ductility of them is higher than that of wrought. However, tensile properties of samples manufactured by island scanning are lowest due to defects (e.g., pores, spatters) at the overlap of islands. Abstract : Different scanning strategies change the direction of the temperature gradient within laser powder bed fusion (LPBF)‐printed Inconel 718 parts, resulting in different grain growth morphology. The ultimate tensile strength of Y‐scan, XY‐scan, and Rot‐scan samples is equivalent to that of the wrought. Properties of Island‐scan samples are lowest due to defects (e.g., pores, spatters) at the overlap of islands.